2007
DOI: 10.1111/j.1600-0609.2007.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment of hematopoietic progenitor cells in patients with coronary heart disease

Abstract: The circulating form of endothelial progenitors cells (EPCs) are derived from bone marrow (BM)-derived hematopoietic stem cells (HSCs). Enhanced mobilization of EPCs was shown to be linked to cardiac diseases. This study investigated whether reduced EPC levels in advanced coronary heart disease (CHD) are secondary to a functional exhaustion of HSCs in the BM or to reduced mobilization. Number and functional properties of EPCs were assessed in 15 healthy controls, and 40 patients with CHD. The colony-forming un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 44 publications
2
28
1
Order By: Relevance
“…This is in line with the decline in bone marrow hematopoiesis observed in patients with coronary artery disease (18). We also showed that inhibition of TNF-␣ almost completely restored CD34 ϩ colony formation and decreased the fraction of apoptotic CD34 ϩ cells in the ischemic CHF mice but not in nonischemic CHF mice.…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with the decline in bone marrow hematopoiesis observed in patients with coronary artery disease (18). We also showed that inhibition of TNF-␣ almost completely restored CD34 ϩ colony formation and decreased the fraction of apoptotic CD34 ϩ cells in the ischemic CHF mice but not in nonischemic CHF mice.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the number and the functional activity of EPCs have been reported to decrease with hypertension, diabetes mellitus and the coexistence of multiple classical cardiovascular risk factors. [4][5][6][7][8][9][10][11]. Levels of EPCs are also inversely correlated to progression of coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, the beneficial outcome of EPC infusion critically depends on the cell number and differentiation factors within the tissue [1]. Correlative studies suggested that number of EPCs inversely correlate to cardiovascular risk factors among apparently healthy people and in patients with coronary heart disease (CHD) [2,3], which show a functional impairment of EPCs, both in the bone marrow as well as when these cells are mobilized into the blood as circulating progenitors [9]. Reduced EPC number has been reported in diabetic patients and in individuals that suffered a stroke [10,11].…”
Section: Introductionmentioning
confidence: 99%